Effect of Protection on Guy Wire Related to Corrosion Defects - Bin Mohamad Lazi, Mohamad Hariz; Mohamad, Zaleha (Journal of Advanced Mechanical Engineering Applications, 2022)
Guy wires are a powerful mechanical tool used widely in all industries. Most of the applications are employed in supporting tall structures such as antenna, communication towers, transmission lines, electric poles, and erecting flare stacks on an oil and gas platform or plant. Severe wind events such as tornadoes are the primary failure in transmitting line structure in many places worldwide. So, this research aims to investigate the effect of different types of guy wire on corrosion defects. There are many lay and strand design types in the production of guy wire. The two most common are the 7-wires and 19-wires lay. There are four samples with four conditions: the first sample is not protected with any material, the second is protected by lubrication using WD-40, the third is protected using rubber hose casing, and the last is protected by a combination of both lubrication and rubber hose casing technique. The result shows that the sample protected by a combination of lubrication and rubber hose casing has no corrosion defect.